2009
DOI: 10.1029/2008jd011298
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and quasi‐biennial variations in the migrating diurnal tide observed by Thermosphere, Ionosphere, Mesosphere, Energetics and Dynamics (TIMED)

Abstract: [1] We present periodic variations of the migrating diurnal tide from Thermosphere, Ionosphere, Mesosphere, Energetics and Dynamics (TIMED) temperature and wind data from 2002 to 2007 and meteor radar data at Maui (20.75°N, 156.43°W). There are strong quasi-biennial oscillation (QBO) signatures in the amplitude of the diurnal tidal temperature in the tropical region and in the wind near ±20°. The magnitude of the QBO in the diurnal tidal amplitude reaches about 3 K in temperature and about 7 m/s (Northern Hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
172
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(202 citation statements)
references
References 46 publications
28
172
1
1
Order By: Relevance
“…(3). Here, we set Pr = 1 and η max = 100, 150, 200 m 2 s −1 , which are similar to previous study values of 10-1000 m 2 s −1 (Hocking, 1987;Xu et al, 2009). The total diffusion which includes both molecular diffusion and eddy diffusion is shown in Fig.…”
Section: Effects Of Eddy Diffusionmentioning
confidence: 50%
“…(3). Here, we set Pr = 1 and η max = 100, 150, 200 m 2 s −1 , which are similar to previous study values of 10-1000 m 2 s −1 (Hocking, 1987;Xu et al, 2009). The total diffusion which includes both molecular diffusion and eddy diffusion is shown in Fig.…”
Section: Effects Of Eddy Diffusionmentioning
confidence: 50%
“…However, in contrast, Xu et al (2009a) came to a different conclusion about the role of gravity waves. They found that the tropical zonal wind variations associated with the QBO had little effect on the filtering of gravity waves because the effect was masked by the larger magnitude winds in the upper stratosphere.…”
Section: Discussionmentioning
confidence: 97%
“…Gurubaran et al (2009) similarly found no trace of QBO signatures in tidal amplitudes over Kauai, but found strong QBO signals in tidal amplitudes over Tirunelveli (8.7 • N, 77.8 • E). Xu et al (2009a) used SABER observations of the diurnal tide to suggest that its amplitudes are modulated by the QBO. Wu et al (2011) considered TIDI observations and reported that the semidiurnal response to the QBO was much smaller than the response of the diurnal tide.…”
Section: R N Davis Et Al: Mesospheric Tides Over Ascension Islandmentioning
confidence: 99%
“…Therefore, it has been widely applied in studies of atmospheric structures (Xu et al, 2007a, b;Dou et al, 2009;Gan et al, 2012), GWs (Preusse et al, 2006;John and Kumar, 2012), tides (Zhang et al, 2006;Pancheva et al, 2009;Xu et al, 2009) and PWs . Garcia et al (2005) and Li et al (2008) also studied QTDWs based on SABER observations.…”
Section: Y Y Huang Et Al: Global Climatological Variability Of Quamentioning
confidence: 99%